A state of the art of flat‐slab frame tests for gravity and lateral loading. (17th October 2020) - Coronelli, Dario; Muttoni, Aurelio; Pascu, Ion R.; Ramos, Antonio P.; Netti, Teresa
Abstract: This paper presents a critical review of the state of the art of experimental research concerning the seismic response of reinforced concrete flat slab frames. After a summary of tests on connections, the paper examines tests carried out on frames with gravity and cyclic lateral loading, and shake table tests; scaled specimens and one real scale study are included. A discussion of the results reached so far is provided focusing on the global response, the different load types and effects; the ultimate rotations at failure in relation to the gravity shear and a classification of different failure modes for different types of connections. Based on this analysis, the research needs are highlighted. An experimental program launched to address these open questions is described. Further open topics are highlighted.